FASSIOLYOZ QO’ZG’ATUVCHILARI VA ULARNING RIVOJLANISHI - Xalilova M.F., Xalilova M.F.; Xosilova G.A., Xosilova G.A. (Actual problems and prospects of the study of the fauna, 2024)
Fasciolosis is a worm disease of humans and animals caused by fasciolae belonging to the class of trematodes. 15 species of F.hepatica and 9 species of F.gigantica have been found to parasitize mammals in the territory of Uzbekistan. The development of fasciola includes 4 periods. According to the literature, fasciolosis occurs in chronic and acute forms.